The little red dot reflections by Singapore's diplomats - Chang, Li Lin; Koh, Tommy T.B. (Tommy Thong Bee), 1937- (World Scientific Institute of Policy Studies, 2005)
2005 is the 40th anniversary of Singapore's independence. This collection of essays by Singapore's past and present diplomats tells the remarkable story of how this small and vulnerable country has become a stable, prosperous and respected member of the international community